2022
DOI: 10.2215/cjn.11260821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrochlorothiazide and Metformin on Aquaresis and Nephroprotection by a Vasopressin V2 Receptor Antagonist in ADPKD

Abstract: Background and objectivesThe vasopressin V2 receptor antagonist tolvaptan is the only drug that has been proven to be nephroprotective in autosomal dominant polycystic kidney disease (ADPKD). Tolvaptan also causes polyuria, limiting tolerability. We hypothesized that cotreatment with hydrochlorothiazide or metformin may ameliorate this side effect.Design, setting, participants, & measurementsWe performed a clinical study and an animal study. In a randomized, controlled, double-blind, crossover trial, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Whether this can be achieved by limiting protein as well as by limiting salt intake is the subject of clinical investigation [ 42 ]. Experimental evidence suggests that co-prescription with metformin also reduces polyuria during tolvaptan treatment [ 43 ], possibly by a vasopressin-independent upregulation of AQP-2 channels in the collecting duct [ 44 ]. However, in a small-scale cross-over study, the tolerability of metformin appeared less than that of hydrochlorothiazide due to gastrointestinal side effects [ 45 ], and consequently, metformin did not improve quality of life [ 43 ].…”
Section: Improving Currently Available Therapeutic Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether this can be achieved by limiting protein as well as by limiting salt intake is the subject of clinical investigation [ 42 ]. Experimental evidence suggests that co-prescription with metformin also reduces polyuria during tolvaptan treatment [ 43 ], possibly by a vasopressin-independent upregulation of AQP-2 channels in the collecting duct [ 44 ]. However, in a small-scale cross-over study, the tolerability of metformin appeared less than that of hydrochlorothiazide due to gastrointestinal side effects [ 45 ], and consequently, metformin did not improve quality of life [ 43 ].…”
Section: Improving Currently Available Therapeutic Optionsmentioning
confidence: 99%
“…Experimental evidence suggests that co-prescription with metformin also reduces polyuria during tolvaptan treatment [ 43 ], possibly by a vasopressin-independent upregulation of AQP-2 channels in the collecting duct [ 44 ]. However, in a small-scale cross-over study, the tolerability of metformin appeared less than that of hydrochlorothiazide due to gastrointestinal side effects [ 45 ], and consequently, metformin did not improve quality of life [ 43 ]. A third method might be to co-prescribe a thiazide diuretic, such as hydrochlorothiazide.…”
Section: Improving Currently Available Therapeutic Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both hydrochlorothiazide and metformin reduced urine volume after 2 weeks of follow-up (hydrochlorothiazide also improved the quality of life and biomarkers of kidney damage). In addition, a long-term follow-up of mice showed that hydrochlorothiazide reduced polyuria in tolvaptan-treated animals [ 65 ]. Although there is no strong evidence for recommending thiazides as an aquaretic effect attenuator, in a larger published observational study, Kramers et al showed that its use was safe in terms of kidney outcomes, so it can be used at least as a second-line antihypertensive [ 66 ].…”
Section: Tolvaptan Aquaretic Effectsmentioning
confidence: 99%